Production of the Main Celiac Disease Autoantigen by Transient Expression in Nicotiana benthamiana - Marín Viegas, Vanesa S.; Acevedo, Gonzalo R.; Bayardo, Mariela P.; Chirdo, Fernando G.; Petruccelli, Silvana (Frontiers in Plant Science, 2015)
Celiac Disease (CD) is a gluten sensitive enteropathy that remains widely undiagnosed and implementation of massive screening tests is needed to reduce the long term complications associated to untreated CD. The main CD autoantigen, human tissue transglutaminase (TG2), is a challenge for the different expression systems available since its cross-linking activity affects cellular processes. Plant-based transient expression systems can be an alternative for the production of this protein. In this work, a transient expression system for the production of human TG2 in Nicotiana benthamiana leaves was optimized and reactivity of plant-produced TG2 in CD screening test was evaluated. First, a subcellular targeting strategy was tested. Cytosolic, secretory, endoplasmic reticulum (C-terminal SEKDEL fusion) and vacuolar (C-terminal KISIA fusion) TG2 versions were transiently expressed in leaves and recombinant protein yields were measured. ER-TG2 and vac-TG2 levels were 9 to 16 fold higher than their cytosolic and secretory counterparts. As second strategy, TG2 variants were co-expressed with a hydrophobic elastin-like polymer (ELP) construct encoding for 36 repeats of the pentapeptide VPGXG in which the guest residue X were V and F in ratio 8:1. Protein bodies (PB) were induced by the ELP, with a consequent 2 fold-increase in accumulation of both ER-TG2 and vac-TG2. Subsequently, ER-TG2 and vac-TG2 were produced and purified using immobilized metal ion affinity chromatography. Plant purified ER-TG2 and vac-TG2 were recognized by three anti-TG2 monoclonal antibodies that bind different epitopes proving that plant-produced antigen has immunochemical characteristics similar to those of human TG2. Lastly, an ELISA was performed with sera of CD patients and healthy controls. Both vac-TG2 and ER-TG2 were positively recognized by IgA of CD patients while they were not recognized by serum from non-celiac controls. These results confirmed the usefulness of plant-produced TG2 to develop screening assays. In conclusion, the combination of subcellular sorting strategy with co-expression with a PB inducing construct was sufficient to increase TG2 protein yields. This type of approach could be extended to other problematic proteins, highlighting the advantages of plant based production platforms.